Classification of the Main Approaches for Strategic Competitive Advantages in Business Management - Stoyanova, Tsvetana (Research Papers, 2010)
In terms of strongly competitive and open markets, keeping a continuous advantage towards the other business participants comes to be an extremely difficult task and lies within the capabilities of the leaders in the respective sector. In this regard, the study hereinafter tries to reveal the main definitions and approaches considering the strategic superiority of particular business organizations over other; to compare and summarize those approaches; to specify the possibilities for their adaptation in regards with the specific conditions in Bulgaria. The characteristics of the strategic competitive advantages are shown in a consecutive manner. The dynamics of the environment such as risk, profit and superiority, is evaluated through the time factor. The study clarifies the essence and peculiarities of contemporary network organizations, the dynamics of their interrelation with the elements of the external environment as well as the reciprocity with the internal company resources management. These are the grounds on which the matrix of interaction is defined and presented as a "general model of strategic management" through which the strategic superiority can be formed and sustained.